PENGARUH INOVASI PRODUK DAN DIVERSIFIKASI PRODUK TERHADAP LOYALITAS PELANGGAN PADA UD. KLINDOCARE DURI - M. Taufiq Bupi Aldiva; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much influence product innovation and product diversification have on customer loyalty. The sample in this study was taken as many as 90 respondents who were determined using the Slovin formula. Data collection techniques in this study using interview methods and questionnaires filled by visitors UD. Klindocare. Data obtained using simple regression analysis and multiple regression analysis. The results of this study indicate that product innovation has a significant effect on customer loyalty. Product diversification has a significant effect on customer loyalty. And simultaneously product innovation and product diversification have a significant effect on customer loyalty.Keywords: Product Innovation, Product Diversification, and Customer Loyalty